Mongolia : Growing without Undue Borrowing - Enhancing Efficiency of Spending and Revenue - World Bank Group (World Bank, Washington, DC, 2019)
This report, the full PER, aims to undertake a detailed analysis of the recent trends in publicexpenditures and revenue with a view to helping Mongolia’s policy makers and opinion leaders identify the main priorities for a successful implementation of its ongoing recovery program. It also intends to strengthen the fiscal foundation of rapid and inclusive growth to help achieve the objectives of the SDV 2030. Furthermore, the PER also reviews the spending needs of key sectors such as health and education, which play an essential role in the long-term development of the country and the fight against poverty.